Decreased bacterial growth on titanium nanoscale topographies created by ion beam assisted evaporation - Stolzoff M (Dove Medical Press, 2017)
Michelle Stolzoff,1 Jason E Burns,2 Arash Aslani,2 Eric J Tobin,2 Congtin Nguyen,1 Nicholas De La Torre,3 Negar H Golshan,3 Katherine S Ziemer,3 Thomas J Webster1,3,4 1Department of Bioengineering, Northeastern University, Boston, 2N2 Biomedical, Bedford, MA, 3Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 4Center of Excellence for Advanced Materials Research, University of King Abdulaziz, Jeddah, Saudi Arabia Abstract: Titanium is one of the most widely used materials for orthopedic implants, yet it has exhibited significant complications in the short and long term, largely resulting from poor cell–material interactions. Among these many modes of failure, bacterial infection at the site of implantation has become a greater concern with the rise of antibiotic-resistant bacteria. Nanostructured surfaces have been found to prevent bacterial colonization on many surfaces, including nanotextured titanium. In many cases, specific nanoscale roughness values and resulting surface energies have been considered to be “bactericidal”; here, we explore the use of ion beam evaporation as a novel technique to create nanoscale topographical features that can reduce bacterial density. Specifically, we investigated the relationship between the roughness and titanium nanofeature shapes and sizes, in which smaller, more regularly spaced nanofeatures (specifically 40–50 nm tall peaks spaced ~0.25 µm apart) were found to have more effect than surfaces with high roughness values alone. Keywords: titanium, nanostructures, bacteria, bone ingrowth, surface roughness, IBAD